Resilience Engineering Oder von der Kunst, in der zivilen Sicherheitsforschung mit Komplexität umzugehen - Scharte, Benjamin (Sicherheit und Gesellschaft. Freiburger Studien des Centre for Security and Society, 2021)
The increasing complexity of our world makes the occurrence of disruptive events with unforeseeable consequences more likely. The future is characterised by uncertainty; therefore, societies and their critical infrastructures need resilience, understood as generic adaptability thanks to flexibility and loose resources. In this book, the author argues that resilience can be normatively desirable if it is used to combine individual freedom and security. Using this as his premise, he develops a new concept of resilience for civil security research and shows how the engineering sciences can implement it through system principles such as diversity, modularity, decentralisation and redundancy.